Incentive-elicited striatal activation in adolescent children of alcoholics - Bjork, James M.; Knutson, Brian; Hommer, Daniel W. (Addiction (Abingdon, England), 2008)
ABSTRACT Aims  Deficient recruitment of motivational circuitry by non‐drug rewards has been postulated as a pre‐morbid risk factor for substance dependence (SD). We tested whether parental alcoholism, which confers risk of SD, is correlated with altered recruitment of ventral striatum (VS) by non‐drug rewards in adolescence. Design  During functional magnetic resonance imaging, adolescent children of alcoholics (COA; age 12–16 years) with no psychiatric disorders (including substance abuse) and similarly aged children with no risk factors responded to targets to win or avoid losing $0, $0.20, $1, $5 or a variable amount (ranging from $0.20 to $5). Results  In general, brain activation by either reward anticipation or outcome notification did not differ between COA and age/gender‐matched controls. Cue‐elicited reward anticipation activated portions of VS in both COA and controls. In nucleus accumbens (NAcc), signal change increased with anticipated reward magnitude (with intermediate recruitment by variable incentives) but not with loss magnitudes. Reward deliveries activated the NAcc and mesofrontal cortex in both COA and controls. Losses activated anterior insula bilaterally in both groups, with more extensive right anterior insula activation by losses in controls. NAcc signal change during anticipation of maximum rewards (relative to non‐reward) correlated positively with both Brief Sensation‐Seeking Scale scores and with self‐reported excitement in response to maximum reward cues (relative to cues for non‐reward). Conclusions  Among adolescents with no psychiatric disorders, incentive‐elicited VS activation may relate more to individual differences in sensation‐seeking personality than to presence of parental alcoholism alone. Future research could focus on adolescents with behavior disorders or additional risk factors.